A novel strategy for site selective spin-labeling to investigate bioactive entities by DNP and EPR spectroscopy - Kevin Herr (Nature Portfolio, 2021)
Abstract A novel specific spin-labeling strategy for bioactive molecules is presented for eptifibatide (integrilin) an antiplatelet aggregation inhibitor, which derives from the venom of certain rattlesnakes. By specifically labeling the disulfide bridge this molecule becomes accessible for analytical techniques such as Electron Paramagnetic Resonance (EPR) and solid state Dynamic Nuclear Polarization (DNP). The necessary spin-label was synthesized and inserted into the disulfide bridge of eptifibatide via reductive followed by insertion by a double Michael addition under physiological conditions. This procedure is universally applicable for disulfide containing biomolecules and is expected to preserve their tertiary structure with minimal change due to the small size of the label and restoring of the previous disulfide connection. HPLC and MS analysis show the successful introduction of the spin label and EPR spectroscopy confirms its activity. DNP-enhanced solid state NMR experiments show signal enhancement factors of up to 19 in 13C CP MAS experiments which corresponds to time saving factors of up to 361. This clearly shows the high potential of our new spin labeling strategy for the introduction of site selective radical spin labels into biomolecules and biosolids without compromising its conformational integrity for structural investigations employing solid-state DNP or advanced EPR techniques.